Macrophage Stimulated by Low Ambient Temperature Hasten Tumor Growth via Glutamine Production - Eun-Ji Lee; Tae-Wook Chung; Keuk-Jun Kim; Boram Bae; Bo-Sung Kim; Suhkmann Kim; Dongryeol Ryu; Sung-Jin Bae; Ki-Tae Ha (Biomedicines, 2020)
Ambient temperature can regulate the immune response and affect tumor growth. Although thermoneutral caging reduces tumor growth via immune activation, little attention has been paid to the tumorigenic effect of low temperature. In the present study, tumor growth was higher at low ambient temperature (4 °C for 8 h/d) than at the standard housing temperature (22 °C) in allograft models. Low temperature-stimulated tumor growth in mice was reduced by monocyte depletion using clodronate liposomes. Proliferation was considerably greater in cancer cells treated with 33 °C-cultured RAW264.7 cell-conditioned media (33CM) than in cells treated with 37 °C-cultured RAW264.7 cell-conditioned media (37CM). Additionally, glutamine levels were markedly higher in 33CM-treated cells than in 37CM-treated cells. We further confirmed that the addition of glutamine into 37CM enhanced its effects on cancer cell proliferation and glutamine uptake inhibition ameliorated the accelerated proliferation induced by 33CM. Consistently, the inhibition of glutamine uptake in the allograft model exposed to low temperature, effectively reduced tumor volume and weight. Collectively, these data suggest that the secretion and utilization of glutamine by macrophages and cancer cells, respectively, are key regulators of low temperature-enhanced cancer progression in the tumor microenvironment.